ANOMALIES IN THE COMPOSITION OF BAIKAL PORE WATERS - Granina L.Z.; Callender E.; Lomonosov I.S.; Mats V.D.; Golobokova L.P. (My University, 2001)
Anomalies in pore water composition have been found in the 100 m long core BDP-93 that was drilled in southern Lake Baikal, in four piston cores (1 to 8 m in length) taken from the same region, and in recent sediments from Frolikha Bay, a. hydrothermal vent site in northern Lake Baikal. Pore water anomalies are manifested as significant increases in concentration of sulfates, bicarbonates, chlorides, and the ions of alkali and alkali-earth metals. Anomalies were found at different depths below the sediment-water interface (from centimeters to tens of meters), and the level of pore water enrichment in these components varies from station to station. Anomalies have specific features in each of the Lake Baikal basins. It is shown that there is a genetic relationship between subaquatic and terrestrial centers of thermal-water discharge in northern Lake Baikal. These anomalous pore-water concentrations are presumably due to the leaching of ambient sediments. In southern Lake Baikal, in the Selenga river delta, ground waters of specific composition that are relics of ancient salt lakes could serve as a source of anomalous concentrations in pore-water components. Their influence may be realized through the extensive zones of increased permeability.